Mechanistic Insights Delineating the Role of Cholesterol in Epithelial Mesenchymal Transition and Drug Resistance in Cancer - Abdulla, Naaziyah; Vincent, C. Theresa; Kaur, Mandeep (Frontiers in Cell and Developmental Biology, 2021)
Despite the significant advancements made in targeted anti-cancer therapy, drug resistance constitutes a multifaceted phenomenon leading to therapy failure and ultimately mortality. Emerging experimental evidence highlight the role of cholesterol metabolism in facilitating drug resistance in cancer. This review aims to describe the role of cholesterol and its downstream metabolites in facilitating multi-drug resistance in cancer. We focus on specific signaling pathways that contribute to drug resistance and the link between these pathways and cholesterol. Additionally, we briefly discuss the molecular mechanisms related to the epithelial-mesenchymal transition (EMT), and the documented link between EMT, metastasis, and drug resistance. We illustrate this by specifically focusing on hypoxia and the role hypoxia plays in influencing cellular cholesterol content following EMT induction. Finally, we also provide preliminary findings delineating the crucial role of cholesterol in EMT and discuss whether targeting cholesterol could serve as a novel means of combatting drug resistance in cancer progression and metastasis.